Diagnosis and Treatment of Adrenocortical Oncocytoma: Case Report of Five Cases and Review of the Literature - Dong, Dexin; Liu, Xiao; Ji, Zhigang; Li, Hanzhong (Frontiers in Oncology, 2019)
Objective: To investigate the diagnosis and treatment of adrenocortical oncocytoma, and have a literature of review. Materials and Methods: The clinical data of 5 cases of adrenocortical oncocytoma treated in our hospital was retrospectively analyzed. The clinical manifestations, imaging examination, endocrine examination, and pathological results were analyzed respectively. Results: Oncocytic adrenocortical neoplasms are extremely rare. Oncocytic adrenocortical neoplasms are usually discovered incidentally, only the tumors with endocrine function could exhibit specific manifestations. No specific imageological features of oncocytic adrenocortical neoplasms have been found. Conclusions: The diagnosis of adrenocortical oncocytoma mainly depends on the pathological examination. Surgical resection is the main treatment method.